Impact of the Coronavirus Lockdown on Older Adolescents Engaged in a School-Based Stress Management Program: Changes in Mental Health, Sleep, Social Support, and Routines. Issue 4 (5th April 2021) - Marques, Sara Schjølberg; Braidwood, Ruth
Abstract: The mental health effects of the coronavirus pandemic are likely to be significant and sustained, especially for those who experience adversity or preexisting mental health difficulties. This article examines the experiences of older adolescents during the United Kingdom government's "lockdown" period (April 2020 to June 2020) on mental health, social support, sleep, and routines using both quantitative and qualitative methods. Participants were enrolled in DISCOVER, a school-based stress management program, in London ( N = 107; 72 percent Black, Asian, or minority ethnicity). The Coping with COVID-19 questionnaire was developed and administered online. Changes in mental health, sleep, and routines were reported during the lockdown period as well as increased worry about family members' physical and mental health. Positive experiences of the lockdown period included improvements in quality of relationships and increased time to spend on hobbies. Participants reported the use of cognitive–behavioral therapy techniques for coping. Results have implications for supporting older adolescents during the pandemic, including on their return to school.